DIAGNOSTICS AND TREATMENT IN THE SCIENTIFIC RESEARCH CHILD AND FAMILY PSYCHIATRY, PSYCHOTHERAPY, PSYCHOLOGY, MEDICAL AND PSYCHOSOCIAL REHABILITATION INSTITUTE AT THE MODERN LEVEL - Rakhmanov, V.M.; Rakhmanov, V.V. (Sworld-Us Conference proceedings, 2022)
This paper presents the development of the most rational methods of medical and psychosocial rehabilitation of patients with limited and functional disorders, which is one of the most important tasks of medicine.As a result of many years of research and